Ocena poziomu wiedzy pacjentów z chorobą nadciśnieniową w zakresie profilaktyki i powikłań nadciśnienia tętniczego = Evaluation of the level of knowledge of patients with hypertensive disease in the prevention and complications of hypertension - Sawicka, Katarzyna; Szczepańska, Justyna; Łuczyk, Robert; Wawryniuk, Agnieszka; Prasał, Marek (Journal of Education, Health and Sport, 2016)
Sawicka Katarzyna, Szczepańska Justyna, Łuczyk Robert, Wawryniuk Agnieszka, Prasał Marek. Ocena poziomu wiedzy pacjentów z chorobą nadciśnieniową w zakresie profilaktyki i powikłań nadciśnienia tętniczego = Evaluation of the level of knowledge of patients with hypertensive disease in the prevention and complications of hypertension. Journal of Education, Health and Sport. 2016;6(12):296-321. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200246 http://ojs.ukw.edu.pl/index.php/johs/article/view/4059 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 09.12.2016. Accepted: 11.12.2016. Ocena poziomu wiedzy pacjentów z chorobą nadciśnieniową w zakresie profilaktyki i powikłań nadciśnienia tętniczego Evaluation of the level of knowledge of patients with hypertensive disease in the prevention and complications of hypertension Katarzyna Sawicka1, Justyna Szczepańska1, Robert Łuczyk1, Agnieszka Wawryniuk1, Marek Prasał2 1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 1 Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin 2 Katedra i Klinika Kardiologii, Uniwersytet Medyczny w Lublinie 2 Department of Cardiology, Medical University of Lublin Streszczenie Wstęp. Nadciśnienie tętnicze to problem, z którym zmaga się cały świat. Polskie społeczeństwo odznacza się wysokim odsetkiem zachorowań na nadciśnienie tętnicze. Jest to 29% dorosłych Polaków, co stanowi około 8,6 miliona osób. Celem pracy była ocena poziomu wiedzy pacjentów z chorobą nadciśnieniową w zakresie profilaktyki i powikłań nadciśnienia tętniczego. Materiał i metoda. Badaniem objęto 110 osób chorujących na nadciśnienia tętnicze. Badaną grupę stanowiły osoby powyżej 18 roku życia. Badania ankietowe trwały od kwietnia do czerwca 2016 roku. W pracy zastosowano metodę sondażu diagnostycznego. Materiał badawczy zebrano za pomocą techniki ankietowania. W pracy wykorzystano kwestionariusz ankiety własnego autorstwa. Kwestionariusz składał się z 27 pytań zamkniętych oraz 12 pytań metryczkowych. Na wstępie przybliżono ankietowanym cel badania. Poinformowano również o zasadzie anonimowości uczestnictwa w badaniu. Wnioski. 1. Kobiety posiadały większą wiedzę na temat nadciśnienia tętniczego niż mężczyźni. 2. Największą wiedzą w zakresie profilaktyki i powikłań nadciśnienia tętniczego miały osoby w wieku 50 - 70 lat. 3. Zdecydowanie większą wiedzę na temat profilaktyki i powikłań nadciśnienia tętniczego mają osoby mieszkające w mieście. 4. Osoby z wyższym wykształceniem cechowały się większą wiedzą na temat nadciśnienia tętniczego niż te z wykształceniem średnim czy podstawowym, co było istotne statystycznie. 5. Większy poziom wiedzy odnośnie nadciśnienia tętniczego mieli respondenci, którzy ocenili swoje warunki materialne jako dobre. 6. Czas trwania choroby koreluje z poziomem wiedzy na jej temat (osoby chorujące dłużej niż 5 lat mają większa wiedzę na temat nadciśnienia tętniczego). Słowa kluczowe: profilaktyka, nadciśnienie tętnicze, wiedza o chorobie Abstract Admission. Hypertension is a problem that faces the whole world. Polish society has a relatively high percentage of cases of hypertension. This is 29% of adult Poles, which is about 8.6 million people. The aim of the study was the price level of knowledge of patients with hypertensive disease in the prevention of complications of hypertension. Material and methods. The study involved 110 people suffering from arterial hypertension. The study group consisted of persons over 18 years old. A survey lasted from April to June 2016 year. The study used a method of diagnostic survey, a research tool was a questionnaire by their own. The research material was collected by surveying techniques. The study used a survey of his own authorship. The questionnaire consisted of 27 closed questions and 12 demographic questions. At the outset brought closer surveyed goal of this research. They were also informed about the principle of anonymity to participate in the study. Conclusions. 1. Women have greater knowledge of hypertension than men. 2. The greatest knowledge of prevention and complications of hypertension were people aged 50 - 70 years. 3. Definitely more knowledge about prevention and complications of hypertension are people living in the city. 4. People with higher education were characterized by a greater knowledge of hypertension than those with secondary or primary, which was statistically significant. 5. A greater level of knowledge about hypertension were respondents who rated their material conditions as good. 6. The duration of the disease correlates with the level of knowledge about it (people suffering from more than 5 years have a greater knowledge about hypertension). Key words: prevention, hypertension, knowledge about the disease